Influence of the commensal gastropod Crepidula plana on shell choice by the marine hermit crab Pagurus longicarpus, with an assessment of the degree of stress caused by different eviction techniques. - Pechenik, Jan A.; Diederich, Casey M.; Burns, Robert.; Pancheri, Francesco Q.; Dorfmann, Luis. (Tufts University. Tisch Library., 2017)
Hermit crabs are notoriously choosy about the gastropod shells they live in. Many periwinkle shells at Nahant, Massachusetts, U.S.A. contain the gastropod Crepidula plana, which forms a thin flat shell inside the periwinkle shell. This study examined how the presence of C. plana affected shell selection behavior by the hermit crab Pagurus longicarpus: naked hermit crabs were offered different combinations of shells, including some containing C. plana and some that had been drilled by naticid gastropods, and their choices were recorded. Because we had to evict hermit crabs from their shells before conducting our choice tests, we also determined rates of recovery from five commonly used shell eviction techniques. No hermit crabs were successfully evicted using low salinity seawater. For the other techniques used, hermit crabs took significantly longer to recover after being removed by gentle but continuous pulling on the carapace and appendages than after being removed by immersion in heated seawater, cracking the shell using a vise, or prodding the hermit crab in the abdomen through a hole drilled in the shell. Even so, most hermit crabs recovered from all of the stresses tested within 20 h, and from at least some stresses within 2-6 h. If shells are to be re-used for experiments, heating seawater is the best technique for evicting P. longicarpus; otherwise, cracking the shell using a vise is recommended. When provided with intact shells and similarly-sized shells containing adult C. plana, all of the hermit crabs chose shells without C. plana, and did so within only about 30 min. However, given a choice between shells housing C. plana and those bearing drill holes-shells which they normally avoid-the hermit crabs were about evenly divided in their choice of shells, and many of the hermit crabs never made a final decision even after 18 or 19 h, suggesting that the presence of C. plana greatly reduces shell attractiveness and suitability. The presence of C. plana increased total shell weight and reduced internal shell volume considerably, and also weakened the shell substantially, likely making the hermit crabs more vulnerable to predators; all of these factors may play a role in selecting for the intense avoidance behavior exhibited by this species for periwinkle shells bearing C. plana.